2014
DOI: 10.1590/1413-812320141910.09802014
|View full text |Cite
|
Sign up to set email alerts
|

Implicações do desenvolvimento econômico no trabalho, ambiente e saúde em comunidades portuárias no Ceará, Brasil

Abstract: Este estudo discute aspectos do desenvolvimento econômico e as implicações no trabalho, ambiente e saúde em comunidades circunvizinhas ao Complexo Industrial e Portuário do Pecém no Ceará. Adotamos como estratégia metodológica a investigação qualitativa, realizando uma pesquisa participante, com análise documental e grupo focal. Os discursos dos sujeitos envolvidos no trabalho de campo foram analisados como representação de suas percepções acerca das transformações ocorridas no território e as repercussões sob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 2 publications
0
6
0
9
Order By: Relevance
“…The references used were: Comprehensive Sociology and Daily Life, such as postmodernity, tribe, ethics of aesthetics, powers, limits and, especially, Theoretical Assumptions and Sensitivity 15 ; and the ergological approach to understanding "human activity" 22 . Regarding the methodological framework of analysis of the collected data, it is observed that most used content analysis 13,[16][17][18][19]22,25,26 ; one study used speech analysis 20 ; another study used Ergonomic Analysis of Work 21 ; one study 23 used the hermeneutic-dialectical approach; another 24 used only the hermeneutic approach; other authors 27 used the analysis of the Collective Subject Discourse; and, finally, two studies 14,28 did not use a specific analysis reference.…”
Section: Studies Conducted In Brazilmentioning
confidence: 99%
“…The references used were: Comprehensive Sociology and Daily Life, such as postmodernity, tribe, ethics of aesthetics, powers, limits and, especially, Theoretical Assumptions and Sensitivity 15 ; and the ergological approach to understanding "human activity" 22 . Regarding the methodological framework of analysis of the collected data, it is observed that most used content analysis 13,[16][17][18][19]22,25,26 ; one study used speech analysis 20 ; another study used Ergonomic Analysis of Work 21 ; one study 23 used the hermeneutic-dialectical approach; another 24 used only the hermeneutic approach; other authors 27 used the analysis of the Collective Subject Discourse; and, finally, two studies 14,28 did not use a specific analysis reference.…”
Section: Studies Conducted In Brazilmentioning
confidence: 99%
“…The results were used to support decisions that promoted sustainable development in port cities (Chen & Nuo, 2013). Bezerra et al. (2014) discussed the economic development of the Port of Pecém and Industrial Complex in Ceara, Brazil, and its impact on employment, environment, and health.…”
Section: Introductionmentioning
confidence: 99%
“…The results were used to support decisions that promoted sustainable development in port cities (Chen & Nuo, 2013). Bezerra and co-workers discussed the economic development of the Port of Pecém and Industrial Complex in Ceara, Brazil, and its impact on employment, environment, and health (Bezerra et al, 2014). Felsenstein and co-workers used microscopic simulation models and statistical estimates to determine the relationship between expansion of the Haifa Port and expected future land use (Felsenstein et al, 2014).…”
Section: Introductionmentioning
confidence: 99%